Biomimetic porous hydrogel scaffolds enabled vascular ingrowth and osteogenic differentiation for vascularized tissue-engineered bone regeneration. (June 2022) - Wu, Xiaodi; Huo, Yingying; Ci, Zheng; Wang, Yahui; Xu, Wei; Bai, Baoshuai; Hao, Junxiang; Hu, Guanhuai; Yu, Mengyuan; Ren, Wenjie; Zhang, Yixin; Hua, Yujie; et al.
Highlights: The design for vascularized bone regeneration is to fabricate a porous hydrogel scaffold with osteogenic and angiogenic biomimetic microenvironments. The bone-biomimetic porous hydrogels effectively support the survival, spreading, and osteogenic differentiation of BMSCs. The bone-biomimetic porous hydrogels have a satisfactory effect on the promotion of vascularized bone regeneration in the ectopic subcutaneous environment. The bone-biomimetic porous hydrogels successfully repair the skull bone defects in situ . Abstract: The construction of vascularized tissue-engineered bone (VTEB ) has been a promising alternative for bone defect repair but remains a remarkable challenge. To date, there have been very limited breakthroughs in VTEB regeneration based on hydrogel scaffolds due to nutrient exchange obstacle caused by a dense hydrogel network, as well as the lack of an osteogenic microenvironment and vascularized pipeline. Here, we developed a novel strategy to prepare porous hydrogel scaffolds with bone biomimetic microenvironments to promote vascular ingrowth and osteogenic differentiation for VTEB regeneration. Based on the phase-separation void-formation technology, porous hydrogel scaffolds with satisfactory mass transport capability were conveniently prepared using gelatin methacryloyl (GelMA ) and poly (ethylene oxide) (PEO ) emulsified two-phase aqueous solutions. By further combining the osteogenic ingredient, decalcified bone matrix (DBM ) particles, and poly (lactic-co-glycolic acid)-encapsulated angiogenic vascular endothelial growth factor (PLGA /VEGF ) microspheres, the porous hydrogel scaffolds with biomimetic osteogenic/angiogenic microenvironments were successfully constructed. Moreover, the osteogenic/angiogenic designs based on the DBM particles, porous structure, and VEGF -released microspheres efficiently enhanced the survival, spreading, migration, and osteogenic differentiation of BMSCs in the hydrogels in vitro, and significantly prompted bone regeneration of BMSC-laden hydrogels in vivo . More importantly, in situ bone defects in a rabbit skull model were successfully repaired with VTEB regenerated by BMSC-laden biomimetic porous hydrogels. This study developed a novel bone-biomimetic porous hydrogel scaffold, which provided promising strategies for ectopic VTEB regeneration and in situ bone defect repair.